Perkembangan Layanan Pertanahan pada Badan Pertanahan Nasional Melalui Program Proyek Operasi Nasional Agraria (PRONA) dan Pendaftaran Tanah Sistematis Lengkap (PTSL) - Esha Kurnia Roustantia; Deviana Cantika; Kurniati Kurniati; Kiki Amaliah (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Legal certainty in land ownership certification in Indonesia is a crucial aspect of protecting citizens' rights. This study aims to analyze the legal certainty provided by the Complete Systematic Land Registration (PTSL) program and the National Agrarian Operation Project (PRONA) in the context of land registration. Using a qualitative approach, this research examines existing regulations and challenges faced in the implementation of both programs. The findings indicate that although land certificates issued through PTSL and PRONA provide legal strength, there remains a potential for disputes arising from third-party dissatisfaction. Therefore, further efforts are needed to strengthen legal certainty guarantees in land ownership in Indonesia.